Extremal topological indices of some nanostructures - Shivani Rai; Biswajit Deb; Zahid Raza; Sourav Mondal (Heliyon, 2023)
In this work, general formulas of degree-based and neighborhood degree sum-based topological indices for a 2D lattice of H-Naphtalenic nanotubes and pent-heptagonal nanosheets are determined. As an example, six neighborhood degree sum-based topological indices are computed using the obtained formula. Furthermore, the extremal cases of these nanostructures with a fixed number of blocks are characterized for a given degree-based or neighborhood degree sum-based topological index. Also a visual comparison of these indices is shown. Additionally, it is demonstrated how beneficial the indices are for representing structure-property relationships.